Do psychological factors and sedentary activities influence physical activity level? Findings from Malaysian adolescents - Leong, In Tyng; Mohd Zulkefli, Nor Afiah; Md Said, Salmiah (Informa UK Limited, 2020)
Regular physical activity provides important health benefits. However, adolescents reduced their physical activity level as they grown up and eventually may develop chronic diseases. Psychological factors and sedentary activities influence physical activity level. A cross-sectional study using a clustered random sampling method was conducted to identify the association between sedentary activities and psychological factors on physical activity level among 1158 Malaysian adolescents (aged 16–17 years) in Selangor. Participants completed a self-administered questionnaire. The prevalence of physical activity level was 47.40%, 39.40% and 13.20% for high, moderate and low levels, respectively. The psychological factors of self-esteem (χ2 = 17.927, df = 2, p < 0.001) and physical activity self-efficacy (F (2, 1155) = 43.570, p < 0.001) were significantly related to physical activity level but not for sedentary activities. The predictor variables for physical activity are suggesting that physical activity self-efficacy may take into consideration for future health programme implementation.